Why does waste Separation at Source Initiative (SSI) did not fully commission in Malaysia? An exploratory preliminary study - Razi, Hafierul Hafiz Md; Roslly, Khairil Adam; Jurimi, Salehhuddin; Sharkawi, Sharizan (Journal of Entrepreneurship, Business and Economics, 2022)
The Separation at Source Initiative (SSI) was launched and became effective in September 2015 under the Solid Waste and Public Cleansing Management Act 2007 (Act 672). Malaysian households were required to participate by implementing waste separation at home, which fell under the classification of waste minimization and production goals. This qualitative research attempted to explore why the Separation at Source Initiative (SSI) did not fully commission in Malaysia. A content analysis approach was conducted to explore the obstacles and challenges of the citizen's participation in the SSI program in Klang Valley, Malaysia. Five individuals participated in this pilot study where data was collected using in-depth interviews. Several open-ended and probing questions were asked to elicit responses and experiences from the participants. Data collected was then analysed using Braun and Clarke’s thematic analysis, where units of meaning were identified from the participants’ responses. Creation of initial codes and categories were then developed and several themes had emerged from the data analysis process. Findings revealed that lack of enforcement, facilities, awareness and incentives as some of the barriers for participating in the SSI. Suggestions for better participation in SSI were also proposed to the rightful stakeholders in ensuring successful implementation of the program. Research paper Keywords: Separation at Source Initiative (SSI); waste minimization; waste management;  Solid Waste Management (SWM); Municipal Solid Waste (MSW); Sustainable Development Goals (SDGs) Reference to this paper should be made as follows: Razi, H. H. M., Roslly, K. A., Jurimi, S., & Sharkawi, S. (2022). Why does waste Separation at Source Initiative (SSI) did not fully commission in Malaysia? An exploratory preliminary study. Journal of Entrepreneurship, Business and Economics , 10 (2), 86–109.